Helicobacter pylori resistance in Hainan Province, China: investigating phenotypes and genotypes through whole-genome sequencing - Lv, Yan-Ting; Li, Da; Zhang, Da-Ya; Chen, Shi-Ju; Chen, Run-Xiang; Wang, Yang; Yang, Wei-Zhong; Gao, Lei; Zeng, Jun-Tao; Xiong, Jian-Xin; Huang, Qiu-Ya; Huang, Jing; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Helicobacter pylori is increasingly resistant to antibiotics, significantly lowering eradication rates and posing a major public health challenge. This study investigated the distribution of antibiotic-resistant phenotypes and genotypes of H. pylori in Hainan Province. It determined the minimum inhibitory concentrations (MICs) of six antibiotics using the E-test method and detected resistance genes via Sanger sequencing. Furthermore, we compared resistance detection based on phenotypic analysis and whole genome sequencing (WGS) across 19 clinical isolates of H. pylori. A total of 140 H. pylori strains were isolated. The resistance rates to levofloxacin (LEV), clarithromycin (CLA), and metronidazole (MTZ) were 37.9%, 40.0%, and 93.6%, respectively. Notably, only 3.3% of the strains were susceptible to all six antibiotics. Multidrug-resistant strains accounted for 25.0% of the total, with no resistance detected to amoxicillin (AMX), tetracycline (TET), or furazolidone (FR) during the study period. Genotypic resistance to CLA and LEV showed near-perfect concordance with phenotypic resistance, with Kappa values of 0.910 and 0.938, respectively. Although all isolates were phenotypically sensitive to TET, 16 exhibited a mutation in the 16S rRNA gene (A926G). All strains harboring the R16H/C mutation and truncated rdxA were resistant to metronidazole, demonstrating a specificity of 100%. Therefore, FR, AMX, and TET are recommended as suitable empirical treatment options for H. pylori infections in this region. Genotypic analysis provides a reliable method for predicting resistance to CLA and LEV. WGS proves to be a valuable tool for identifying novel resistance loci in H. pylori and contributes to the phylogenetic classification of strains.